2004
DOI: 10.1128/jvi.78.13.6915-6926.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Biological Analysis of Human Immunodeficiency Virus Type 1 R5 Envelopes Amplified from Brain and Lymph Node Tissues of AIDS Patients with Neuropathology Reveals Two Distinct Tropism Phenotypes and Identifies Envelopes in the Brain That Confer an Enhanced Tropism and Fusigenicity for Macrophages

Abstract: Complete envelope genes were amplified from autopsy brain tissue of five individuals who had died of AIDS and had neurological complications. Lymph node samples were included for two of the patients. Nineteen different envelope clones from the five patients had distinct V1V2 sequences. Thirteen of the envelopes were functional and conferred fusigenicity and infectivity for CD4 ؉ CCR5 ؉ cells. Infectivity and cell-cell fusion assays showed that most envelopes used both CCR5 and CCR3. One brain-derived envelope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
282
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(303 citation statements)
references
References 51 publications
(49 reference statements)
14
282
7
Order By: Relevance
“…However, Peters et al recently published a study concluding that envelopes from primary brain isolates confer lower CD4 dependence and lower sensitivity to inhibition by anti-CD4 antibodies than envelopes derived from peripheral tissues of the same individuals (56). In addition, lower CCR5 and CD4 dependencies have been shown to represent a pathogenic viral phenotype contributing to the neurodegenerative manifestations of AIDS (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Peters et al recently published a study concluding that envelopes from primary brain isolates confer lower CD4 dependence and lower sensitivity to inhibition by anti-CD4 antibodies than envelopes derived from peripheral tissues of the same individuals (56). In addition, lower CCR5 and CD4 dependencies have been shown to represent a pathogenic viral phenotype contributing to the neurodegenerative manifestations of AIDS (25).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition curves showed a lower sensitivity for Bori-15, with statistically significant fourto sixfold-higher IC 50 values than Bori. Decreased sensitivity to inhibition of infection by anti-CD4 antibodies has been recently reported for brain-derived HIV envelopes by Peters et al (56). Additional studies will be required to dissect the role of the individual 8 amino acid changes between Bori and Bori-15 envelopes, especially the four substitutions located in the V1/V2 region, on gp120 conformation and/or flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…The specific pressures that drive the tissue, as well as regional CNS env genetic divergence, remain unclear. Emergence of highly macrophage-tropic viral strains that engage the CD4 and CCR5 receptors differently or have a lower CD4 dependence for entry has been reported in HIV and SIV infection of the brain (27)(28)(29)(30)(31)(32). The need for robust replication in macrophages and infection of CNS-resident cells, such as microglia and astrocytes, that express CCR5 but little or no CD4 (33)(34)(35), therefore, could be a major selective pressure for independent envelope evolution in the brain that contributes to neurological injury.…”
mentioning
confidence: 99%
“…We reported that primary HIV-1 R5 isolates varied in their capacity to infect primary macrophage cultures by over 1,000-fold (33). We also first described a subset of HIV-1 R5 isolates that could infect CD4 ϩ T-cell lines via trace amounts of CCR5 (11), and we recently described HIV-1 R5 envelopes from brain tissues of individuals with neurological complications that were highly fusigenic and tropic for macrophages (27). These latter envelopes are able to exploit low amounts of CD4 and/or CCR5 for infection and contrast emphatically with envelopes from immune tissue (lymph node) that failed to confer macrophage infection and required higher amounts of CD4 for infection.…”
mentioning
confidence: 99%